PENGEMBANGAN METODE SINEKTIF PADA TEKS BERITA KELAS VIII SMP MUHAMMADIYAH KUPANG - arasy anshari; Harry Surahman; Endang Sumarti (Paradigma: Jurnal Filsafat, Sains, Teknologi, dan Sosial Budaya, 2023)
Understanding news text is not just to know a news. Learning about news text is to attract children's interest in learning Indonesian, and children are also eager to learn by watching or reading news so that there is a willingness and ability of children to think by making news. Writing is a creative process of expressing ideas in the form of written language in review, for example, informing, convincing, or entertaining. This research was conducted using the experimental method. Experimental research consists of three main points, namely: (1) the existence of manipulated independent variables, (2) the existence of control or control of all other variables except the independent variable, and (3) the observation or measurement of the dependent variable as the effect of the independent variable This research design uses the experimental design of Control Group Pre Test-Post Test Design. The results of the analysis and discussion show that there is a significant difference between the news text writing skills of experimental group students who follow learning with the synectic model and control group students who do not follow. The difference can be proven by the calculation results on the posttest scores of the control group and the experimental group which show that the mean of the news text writing skills of the control group students is 76.50, while the experimental group is 78.03. Second, the effectiveness of the synectic model in learning to write news texts is also indicated by the results of the t-test comparison on the pretest and posttest scores in the control group and the experimental group which was 96.97. Both groups experienced an increase in news text writing skills, but the experimental group experienced a greater increase. The average score of the experimental group was 78.03, from the average pretest score of 75.94, while the average score of the control group was 76.50, from the average pretest score of 76.31.